2022
DOI: 10.3390/diagnostics12020517
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Anemia in Patients with Preserved, Mildly Reduced and Recovered Ejection Fraction

Abstract: Data on the relevance of anemia in heart failure (HF) patients with an ejection fraction (EF) > 40% by subgroup—preserved (HFpEF), mildly reduced (HFmrEF) and the newly defined recovered EF (HFrecEF)—are scarce. Patients with HF symptoms, elevated NT-proBNP, EF ≥ 40% and structural abnormalities were registered in the HFpEF-HFmrEF database. We described the outcome of our HFpEF-HFmrEF cohort by the presence of anemia. Additionally, HFrecEF patients were also selected from HFrEF patients who underwent resync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…This inflammatory and congestive environment may also explain the lower haemoglobin levels in patients with high CA 125 levels. Certainly, anaemia is due to multiple factors in HFpEF, which encompass conditions related to iron deficiency, dependency on erythropoietin with chronic kidney disease, inflammation, and volume overload, probably explaining the elevated CA 125 levels 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inflammatory and congestive environment may also explain the lower haemoglobin levels in patients with high CA 125 levels. Certainly, anaemia is due to multiple factors in HFpEF, which encompass conditions related to iron deficiency, dependency on erythropoietin with chronic kidney disease, inflammation, and volume overload, probably explaining the elevated CA 125 levels 32 …”
Section: Discussionmentioning
confidence: 99%
“…Certainly, anaemia is due to multiple factors in HFpEF, which encompass conditions related to iron deficiency, dependency on erythropoietin with chronic kidney disease, inflammation, and volume overload, probably explaining the elevated CA 125 levels. 32 Additionally, our study demonstrated for the first time in a chronic HFpEF patient population a positive correlation be-CV, cardiovascular; ECV, extracellular volume; EDV, end-diastolic volume; eGFR, estimated glomerular filtration rate; eSPAP, estimated systolic pulmonary artery pressure; FGF-23, fibroblast growth factor 23; HDL-C, high-density lipoprotein cholesterol; HFpEF, heart failure with preserved ejection fraction; hsTnT, high-sensitivity troponin T; IQR, inter-quartile range; LA, left atrial; LDL-C, low-density lipoprotein cholesterol; LV, left ventricular; MRA, mineralocorticoid receptor antagonist; NT-proBNP, N-terminal pro-brain natriuretic peptide; NYHA, New York Heart Association; RV, right ventricular; ST2, suppression of tumourigenicity 2; TAPSE, tricuspid annular plane systolic excursion. Values are reported as means ± standard deviations or medians and IQRs (IQR 0.25-0.75).…”
Section: Carbohydrate Antigen 125 Level Elevation As a Marker Of Cong...mentioning
confidence: 99%
“…Anaemia is a crucial finding in patients suffering from HF [ 1 , 30 , 31 ]. Despite many studies correlating anaemia with the prognosis of patients with HF [ 31 , 32 , 33 , 34 ], there is a paucity of data related to the interplay between anaemia and congestion, i.e., the most important clinical feature of patients with HF [ 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia, affecting 15–20% of HFpEF patients, reduces oxygen delivery to tissues, increases cardiac output, and contributes to volume overload and left ventricular remodeling. 28) …”
Section: Comorbidities In Hfmref and Hfpefmentioning
confidence: 99%